W cieniu. Zofii Tołstojowej (1844–1919) i Anny Dostojewskiej (1846–1918) skrywane pisarstwo - Walęciuk-Dejneka, Beata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
The article is bringing the issue of the women’s being up in world, according to Heidegger’s concept „of being – in – world”. In this articule, I write only about women’s form of becoming known in literature through the writing. Such a presence determines female experience, family, social and national roles, love, initiation, rebellious or personal reports, and because of that is sending to the mythical and stereotyped phenomena rooted in the culture. It is also women’s getting to know world. I chose women’s personal notes from the 19th turning point and the 20th century – diaries which they constitute of certain kind reconstruction of the own history and the history of the family. So I will examine only chosen fragments of „Diaries” by Zofia Tołstojowa and „Memories” by Anna Dostojewska.